Educational Administrators’ Competencies Affecting Personnel Management in Schools Under the Office of Prachuap Khiri Khan Primary Educational Service Area 1 - Phiphitrutsameekul, Subhanuth; Chiinathattiyo, Phramaha Kraiwan (Journal of Dhamma for Life, 2026)
This study aimed to (1) examine the level of school administrators’ competencies, (2) investigate the level of personnel management in schools, and (3) analyze the administrators’ competencies affecting personnel management in schools under Prachuap Khiri Khan Primary Educational Service Area Office 1. A quantitative research design was employed. The population comprised 117 schools, from which 90 schools were selected as the sample. The total number of informants was 360, including school administrators, heads of personnel administration, and teachers. The research instrument was a rating-scale questionnaire. Data were analyzed using statistical software, employing frequency, percentage, mean, standard deviation, and multiple regression analysis for hypothesis testing. The findings revealed that: (1) overall, the competencies of school administrators were at a high level. When considered by dimension, teamwork competency ranked highest, followed by the use of technology and innovation, while change management competency ranked lowest. (2) Overall personnel management in schools was also at a high level. Among its dimensions, personnel development ranked highest, followed by personnel separation, whereas personnel maintenance ranked lowest. (3) The competencies of school administrators significantly influenced personnel management in schools at the .01 level of significance. The significant predictors included adaptability and flexibility, the use of technology and innovation, and change management competency. These variables collectively accounted for 70.7% of the variance (R² = 0.707), with a multiple correlation coefficient of 0.841 and a standard error of estimate of 0.268. The predictive equations were as follows: Raw Score Equation: = 0.710 + 0.164 (X3) + 0.202 (X4) + 0.179 (X5) Standard Score Equation: Ẑ = 0.176 (X3) + 0.225 (X4) + 0.195 (X5) The results underscore the critical role of adaptive capacity, technological competency, and change management in enhancing effective personnel management in schools. These findings provide empirical evidence to inform policy and practice aimed at strengthening leadership capacity and improving human resource management in educational institutions.